2017
DOI: 10.2323/jgam.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of H-box region mutants of WalK inert to the action of waldiomycin in <i>Bacillus subtilis</i>

Abstract: The WalK/WalR two-component system is essential for cell wall metabolism and thus for cell growth in Bacillus subtilis. Waldiomycin was previously isolated as an antibiotic that targeted WalK, the cognate histidine kinase (HK) of the response regulator, WalR, in B. subtilis. To gain further insights into the action of waldiomycin on WalK and narrow down its site of action, mutations were introduced in the H-box region, a well-conserved motif of the bacterial HKs of WalK. The half-maximal inhibitory concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In contrast, the addition of 2b, 2h, or 2l increased the MS signal of the collected waldiomycin by about twofold compared to the signal in the presence of only waldiomycin (Fig. 6, columns 5,6,9,10,11,12). These results suggest that the binding of 2b, 2h, or 2l to WalK is not competitive with that of waldiomycin, but rather enhances the binding of waldiomycin.…”
Section: Affinity Selection/mass Spectrometrymentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, the addition of 2b, 2h, or 2l increased the MS signal of the collected waldiomycin by about twofold compared to the signal in the presence of only waldiomycin (Fig. 6, columns 5,6,9,10,11,12). These results suggest that the binding of 2b, 2h, or 2l to WalK is not competitive with that of waldiomycin, but rather enhances the binding of waldiomycin.…”
Section: Affinity Selection/mass Spectrometrymentioning
confidence: 83%
“…The naphthoquinone moiety of waldiomycin is believed to bind to the H-box region of the intracellular dimerization domain of HK (Fig. 2b) [8,9]. This region is present in bacteria but not in mammalian cells, including humans [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutations in MAG 71 ( Firmicutes ) genes involved in cell wall synthesis are consistent with developing resistance via limiting drug uptake. The mutations in WalK contribute to the development of vancomycin resistance in Staphylococcus aureus (Zhu et al 2021), as well as waldiomycin resistance in Bacillus subtilis (Kato et al 2017). MurG encodes an enzyme involved in the biosynthesis of peptidoglycan, a crucial component of bacterial cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…A series of experiments showed that waldiomycin inhibited HK in an ATP-non-competitive manner, suggesting that the binding site of waldiomycin may not be located in the ATP active site in the CA domain. Additionally, more detailed experiments, including nuclear magnetic resonance (NMR) spectroscopy and protein amino acid mutation, indicated that waldiomycin may bind to the H-box region of the DHp domain, which contains the conserved His residue, to inhibit the class-I HKs and suppress the autophosphorylations ( Eguchi et al, 2017 ; Kato et al, 2017 ). The broad-spectrum HK inhibition activities of waldiomycin showed that the H-box could be a promising target for the design of novel broad-spectrum HK inhibitors especially those HKs with the WalK-type H-box region.…”
Section: Novel Histidine Kinase-targeted Antimicrobial Agentsmentioning
confidence: 99%
“…Another important direction for the discovery of new HK inhibitors is to design inhibitors by targeting the DHp domain, which is formed by two long helices (α1 and α2), where α1 contains a phosphorylatable conserved His residue (His391, as shown in Figure 3 ) ( Casino et al, 2014 ). This domain contains His391 is called H-box (shown in Figure 1 , the position of the histidine phosphorylation site is marked with an “H” indicating the H-box region), which is the site of autophosphorylation ( Wang et al, 2013 ; Kato et al, 2017 ). This structural homology of HKs indicates the possibility that multiple TCSs can be inhibited simultaneously by one inhibitor, and decrease the appearance of drug-resistant strains.…”
Section: Introductionmentioning
confidence: 99%